Residues and dissipation of imidacloprid in avocado fruit - Sarmiento-Sarmiento, Guido; Manrique-Nuñez, Horacio; Lipa-Mamani, Luis (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2022)
Imidacloprid is a neonicotinoid insecticide used to control insect pests in avocado (Persea americana); its excessive application could generate residues above the maximum residue limits (MRL) in the fruit, causing a serious health risk to consumers. The objective of this work was to determine the residues and dissipation of imidacloprid in avocado fruit, Hass variety. The treatments were the doses of Imidacloprid (0.5, 1.0 and 1.5 mL.L-1) under the commercial formulation Thunder 350SC and the forms of application (sprayed to foliage and drip at the foot of the plant). There were six treatments in a completely randomized experimental design with three replications and 18 experimental units (plants). Quantification was by HPLC (QuEChERS). The evaluations were carried out on two matrices (avocado fruit peel and pulp) at 1, 3, 7 and 14 days after the application of Imidacloprid. The application of the 0.5 mL.L-1 dose by drip at the foot of the plant resulted in lower residual and a higher percentage of dissipation in both matrices, higher daily dissipation rate in the pulp, with imidacloprid concentrations that did not exceed the MRL (0.7 mg.kg-1). The application of 1.5 mL.L-1 by spraying resulted in higher residual, and in a lower percentage of dissipation in both matrices, with imidacloprid concentrations in the peel exceeding the MRL at 7 and 14 days. In the pulp, none of the treatments exceeded the MRL.